Chemical-Physical Properties Characterization of White Snapper Fish Skin Rambak Crackers Based on Boiling and Drying Duration - Hardoko Hardoko; Sri Utami (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsThe utilisation process of snapper skin from fish fillet industry by products for cracklings was not optimalThe optimization of snapper skin crackling production by boiling and drying methodThe optimal method of snapper skin crackling production was 30 minutes of boiling and sun-drying for 30 hoursAbstractFish skin is a byproduct of fish filet production, its use is still limited, but some of the terrestrial animal skin is partially processed into rambak crackers, which is quite well known in Indonesia. The purpose of this study was to determine the duration of boiling and drying time on the chemical-physical properties of rambak crackers from white snapper skin. The research method used was an experiment with a boiling time treatment of 0, 10, 15, and 20 minutes and drying time with 10, 20, and 30 hours in sunlight. The results showed that the boiling time and drying duration had an effect on the chemical-physical properties of the rambak crackers of white snapper fish skin. The resulting rambak crackers have physical characteristics of 15.13-25.39 N / m2, 70.44-100.07% enlarging capacity, and chemical characteristics of the water content was 1.09-4.95%, protein content of 65.26-70.43%, and fat content of 13.43-15.83%. The best crackers are those which resulted from 30 minutes of boiling and 30 hours of frying process with a fracture limit of 15.13 N/m2, an enlarging capacity of 100.07%, moisture content of 1.09%, protein content of 66.25%, and fat content of 13. 43%.